Synergistic effect of simultaneous dual doping in solvent-free mechanochemical synthesis of polyaniline supercapacitor comparable to the composites with multiwalled carbon nanotube. (16th December 2015) - Bhandari, Subhendu; Khastgir, Dipak
Abstract: This work reveals, for the first time, the synergistic improvement of electrical conductivity and supercapacitive behaviour of PAni prepared via solvent-free solid state synthesis method using the combination of dopants at appropriate ratios. The improvements in electrical and capacitive behaviour are comparable or even better than PAni composites with multiwalled carbon nanotube (MWCNTs). PAni has been prepared via solvent-free synthesis route by simultaneous dual doping with camphorsulfonic acid (CSA) and citric acid (CA) at the different ratios of [CA]:[CSA] as 1:3, 2:2 and 3:1. Dual doped PAni exhibits synergistic improvement in conductivity (up to 4.8 × 10 −2 Scm −1 ) and capacitive behaviour (up to 303.1 Fg −1 ) as well which have been compared with that of PAni/MWCNTs composites containing 2, 4 and 8 wt% MWCNTs. PAni doped with [CA]:[CSA] = 3:1 exhibits higher conductivity than the composite containing 4 wt% MWCNTs, and even higher specific capacitance than the composite with 8 wt% MWCNTs loading. Graphical abstract: Highlights: Simultaneous doping with organic acids in solvent-free synthesis of polyaniline. Synergistic improvement in conductivity and specific capacitance for dual doping. Synergy of dual doping exhibits properties comparable with PAni/MWCNT composites. Easy synthesis method like mechanochemical or solid-state route has been followed.